Fiber-tip photonic crystal for real-time referenced biosensing in serum - Mathias Dolci; Paco Dreverman; Mildred S. Cano-Velázquez; Arthur L. Hendriks; Emiel Veth; P.J. van Veldhoven; Andrea Fiore; Peter Zijlstra (Biosensors and Bioelectronics: X)
Fiber optic sensors have become increasingly well-established due to the many advantages they provide such as immunity to electromagnetic interference, multiplexing capabilities, and remote sensing. The coupling of light with a transducer at the tip of the optical fiber enables the detection of physical and biological parameters. 2D photonic crystals (PhC) can be designed to feature guided-mode resonances (GMR) characterized by a strong electric field at the PhC surface, providing a suitable tool for the detection of local refractive index variations (e.g. biomolecule adsorption). Here, we demonstrate the use of a PhC transferred to the tip of a single-mode fiber for biosensing. The control of surface chemistry provides a sensitive platform for the molecular recognition of antibody biomarkers. By integrating the fiber in a continuous flow platform, the real-time detection of anti-IgG in undiluted serum was achieved, with a limit of detection down to 60 pM. Moreover, the use of a reference channel is demonstrated to correct for signal drifts in real-time due to changes in bulk refractive index. These referenced fiber-tip PhC biosensors may pave the way for fluidic integrated systems in environmental, industrial, and healthcare applications, and open up the possibility of biosensing in the human body by integrating them into catheters.